Database internals a deep dive into how distributed data systems work - Petrov, Alex (Ascent Audio, 2022)
When it comes to choosing, using, and maintaining a database, understanding its internals is essential. But with so many distributed databases and tools available today, it's often difficult to understand what each one offers. With this practical guide, Alex Petrov guides developers through the concepts behind modern database and storage engine internals. Throughout the book, you'll explore relevant material gleaned from numerous books, papers, blog posts, and the source code of several open source databases. You'll discover that the most significant distinctions among many modern databases reside in subsystems that determine how storage is organized and how data is distributed. This book examines: - Storage engines: Explore storage classification and taxonomy, and dive into B-Tree-based and immutable Log Structured storage engines - Storage building blocks: Learn how database files are organized to build efficient storage, using auxiliary data structures - Distributed systems: Learn how nodes and processes connect and build complex communication patterns - Database clusters: Which consistency models are commonly used by modern databases and how distributed storage systems achieve consistency.